Sensory, Microbiological and Biochemical Quality of black pomfrets (Pampus niger) stored in dry ice and ice - G., Jeyasekaran; D., Sukumar; R., Jeya Shakila; R., Anandaraj (Fishery Technology, 2025)
The sensory, microbiological and biochemical quality of black pomfrets (Pampus niger) stored in different ice packages was investigated. Pomfrets packed in dry ice at the ratio of 1:1 (w/w) were found to be sensorialy suitable for consumption when they were stored for 24 h without re-icing. Pomfrets stored in a combination of dry ice and ice at the ratio of 1:0.2:0.5 (w/w/w) and in ice at the ratio of 1:1 (w/w) (as control) were acceptable up to 18 h and 12 h, respectively. Total bacterial load ranged from 104 to 107 cfu/g, while total psychrophiles from 103 to 106 cfu/g. Total lactic acid bacteria varied from 103 to 105 cfu/g. TVB-N and TMA-N contents were within the permissible limit in pomfrets stored in dry ice. Hypoxanthine (Hx) contents ranged from 3.46 to 8.96 mg/lOOg and FFA content varied from 10.35 to 54.34% as oleic acid. Lowest temperature of -110C was recorded in pomfrets stored in dry ice. Packages I and II had 100% C02 inside after one hour of storage.